Resurrection of Caltoris ranrunna (Sonan) from synonymy as a skipper endemic to Taiwan based on COI barcode and morphology - Hsu, Yu-Feng; Xue, Guo-Xi; Lin, Rung-Juen; Huang, Li (Zootaxa, 2019)
Caltoris ranrunna (Sonan, 1936) is resurrected from synonymy of Caltoris cahira austeni (Moore, 1883) to represent a Caltoris species endemic to Taiwan based upon COI barcode divergence and morphological diagnosis in genitalia of both sexes. This species distributes allopatrically from C. cahira of continental Asia and Andamans.